Business Strategy Analysis and Recommendation for Hemyo Photo and Videography - Akbar, Ryan; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2012)
Hemyo photo and videography has been established for 1 year in Bandung with their market segment was in the making of music video clip and promotional video for a product brand. But, because of the market segment and the area location in which they operating have a low buying power it raised a strategy issue for the company to enter a new market segment.Hemyo have to analyze the internal and eternal condition before continuing to do a strategy analysis for the future growth of the company. The methodology analysis used to assess the problem was SFAS Analysis, Strategic Diamond and Porter’s Five Forces. And after the internal and external analysis has completed, it then proceed using the SWOT Analysis.The SFAS analysis shows that Hemyo should focus their strategy based on priority which based on the time factor. The result shows that the short term priority for them is in the Marketing area. The SWOT analysis shows that the company should fix their internal organization before trying to enter a new market.The strategies then managed into implementation plans that being described in detail the steps and the estimated duration. If the proposed strategy does not run as expected, an exit strategy has been prepared which is letting it run dry. Key words: SFAS, Strategic Diamond, Porter’s Five Forces, SWOT